Structural and magnetic properties of bulk Mn2PtSn. (31st October 2018) - Herran, J; Prophet, S; Jin, Y; Valloppilly, S; Kharel, P R; Sellmyer, D J; Lukashev, P V
Abstract: Interplay between structural and magnetic order parameters is one of the key mechanisms of tuning properties of materials intended for device applications in spintronics. Here, using density functional calculations, we study combined effects of tetragonal distortion and non-collinear magnetic order in Mn2 PtSn. We show that this material has two energetically close energy minimums corresponding to tetragonal lattice. In one of these phases, Mn2 PtSn exhibits ferrimagnetic order with nearly fully compensated total magnetic moment, while in the other phase that corresponds to the lowest energy, a non-collinear magnetic arrangement emerges, with very large canting angle of the Mn local magnetic moments. The non-collinear alignment is explained through the interplay of exchange couplings between nearest and next nearest neighbor Mn atoms. Results are compared with those reported in recent literature, both experimental and theoretical.